Multiphase particle-in-cell simulation in severe internal carotid artery stenosis - Sia, Sheau Fung; Zhao, Xuemei; Yu, Yong; Zhang, Yu (Elsevier, 2019)
Internal carotid artery (ICA) stenosis, usually caused by atherosclerosis plaque, restricts the blood supply to the brain and causes cerebral ischemia. The plaque can be stable and asymptomatic, or it can cause embolization. An emboli can break from the plaque and travel to the blood vessels in the brain, causing a transient ischemic attack (TIA) or thromboembolic stroke. To reduce the risk of a stroke, estimation of the blood flow and stress distribution at the ICA stenosis is important. Common diagnostic methods, such as computed tomography (CT) and magnetic resonance imaging (MRI) are only able to provide a stenotic configuration. In addition, conventional image-based computational fluid dynamics (CFD) assumes the blood is a single-phase fluid, ignoring the circulating blood cell particles. This may result in an unreliable estimation of the blood flow and stress distribution at the ICA stenosis. Therefore, a multiphase particle-in-cell (MP-PIC) model was introduced to calculate the plasma flow and blood cell motion separately. The MP-PIC simulation showed a reverse flow, flow stagnation, and flow swigging at the stenosis that was not demonstrated by the single-phase model simulation. Thus, the blood cell motion caused significant temporal and spatial flow oscillation variations at the stenosis and must be considered in a hemodynamic simulation. © 2018 Elsevier B.V.